La arqueología japonesa y la construcción del paradigma ainu -más allá del mito del cazador primitivo - Abad de los Santos, Rafael (Mirai. Estudios Japoneses, 2022)
The present study aims to historiographically analyze the construction of paradigms referring to the ainu culture since the nineteenth century. Since the introduction of modern archeology and Western models of thought in Japan, this culture has been perceived as the material expression of groups of hunters and gatherers who, isolated in the north of the archipelago, maintained a primitive way of life without modifications since prehistoric times. This perception of the ainu culture found its greatest exponent in the work of Watanabe Hitoshi during the 1960s and 1970s. However, the development of archaeological research in the last three decades has made it possible to clarify that the ainu culture emerged around the 13th and 14th centuries as a result of human and commercial interaction. In this sense, it is necessary to distinguish three essential elements: the indigenous communities of Hokkaidō, the wajin bearers of the satsumon culture, and the members of the Okhotsk culture.